Platform switching in two‐implant bar‐retained mandibular overdentures: 1‐year results from a split‐mouth randomized controlled clinical trial. Issue 10 (8th August 2020) - Abou‐Ayash, Samir; Schimmel, Martin; Kraus, Dominik; Mericske‐Stern, Regina; Albrecht, Dominic; Enkling, Norbert
Abstract: Objectives: The concept of platform switching is widely applied in current implant dentistry; however, the influence on peri‐implant bone‐level alterations (ΔIBL), especially in the field of implant overdentures (IODs), remains inconclusive. Therefore, the present study aimed to test the alternative hypothesis that there is an equivalent ΔIBLs at platform‐switching and platform‐matching implant abutments in 2‐implant bar‐retained IODs. Materials and methods: Two interforaminal implants were placed in 32 subjects, who were randomly assigned to either an immediate‐ or a 3‐month post‐placement loading group. Furthermore, one implant in each subject was randomly assigned to receive a platform‐switched abutment (test), and one a platform‐matching abutment (control). The implants were splinted with prefabricated, chairside customized bars. ΔIBL was recorded by using customized radiograph holders at implant placement, implant loading, 3 months, 6 months, and 12 months after loading. Results: After 1 year, equivalent ΔIBL could be identified (test: −0.51 mm ± 0.49 versus control: −0.56 mm ± 0.52; p  < .001). ΔIBL increased over time and was more pronounced in the delayed‐loaded implants (−0.87 mm ± 0.61) relative to the immediately loaded implants (−0.35 mm ± 0.43; p  = .022). Conclusions: The prosthetic concept of platform switching does not necessarily lead to reduced bone loss. Immediate‐loading of implants, primarily splinted with a bar, might be beneficial regarding peri‐implant bone‐level alterations over a short‐term period.